Effects of Blended Instructional Models on Math Performance. (July 2014) - Bottge, Brian A.; Ma, Xin; Gassaway, Linda; Toland, Michael D.; Butler, Mark; Cho, Sun-Joo
A pretest-posttest cluster-randomized trial involving 31 middle schools and 335 students with disabilities tested the effects of combining explicit and anchored instruction on fraction computation and problem solving. Results of standardized and researcher-developed tests showed that students who were taught with the blended units outscored students in Business As Usual classes. Students made the largest gains in computing with fractions and on problems related to ratios, proportions, and geometry. The findings suggest important implications for the way curriculum is designed for middle school students with disabilities who exhibit low performance in math.